Epidemiology of newcastle disease in chicken in the Sultanate Of Oman - Mohammed, Al Sahami Ali Abdullah (2018)
Newcastle disease (ND) remains as one of the major disease in poultry production worldwide. In the Middle East nations including the Sultanate of Oman specifically, the Newcastle disease virus (NDV) is known to have been circulating for the past two decades. Nevertheless, there is little information on the seroprevalence of the disease among chickens as well as the nature of the NDV causing outbreaks in various poultry management systems in Oman. To date, there is a lack of specific study on the epidemiology of ND in Oman. Hence, the objectives of this study were: were to: 1) determine the proportion of ND in the small holder and commercial farms in Oman from 2011-2015; 2) determine the seroprevalence of ND in backyard poultry; 3) determine the risk factors associated with the occurrence of ND and the efficacy of reporting and notification system in Oman; 4) isolate and characterize the NDV from the outbreaks of ND in Oman occurred in 2017; and, 5) assess the economic impact on the poultry sector of Oman due to ND outbreaks. In a retrospective study, the 5-year records of ND outbreaks between 2011 and 2015 were analyzed. In total, number of 1223 farms (mean ± SD, 256 ± 37) and 90,959 birds (mean ± SD, 23,400 ± 452) have been affected with ND between 2011 and 2015. The yearly proportion of ND at the farm level was the highest in 2011, 68% (95%Confidence interval, CI 66-71%) and the lowest was in 2015, 2% (95%CI 1-3%). At bird level, 2014 recorded the highest level of ND cases, 31% (95%CI 30-31%) and 2015 was the lowest (1.2%, 95%CI 1.1-1.2%). Majority of the farm (61%, 95%CI 58-64%) and bird (47%, 95%CI 46.4-47%) cases occurred in Al-Batinah governorate. The highest proportion of ND was in January (21%, 95%CI 19-24%) and lowest in July (0.16%, 95%CI 0-0.4%) with steady increase from August to December. There was a significant difference (P<0.05) in the reported ND cases between years, months and governorates. The backyard poultry had the highest reported outbreaks of ND (70%, 95%CI 68-73%) and lowest in the closed system (5%, 95%CI 4-6%). Farms in backyard system was 47 times more likely to report ND cases (95%CI Odds ratio, OR 35-62) and open system (OR=7, 95%CI 5-9) compared to the close system. Contrarily, birds in backyard system were 1.8 (95%CI 1.7-1.8) times less likely to report ND cases compared to open and close systems. The seroprevalence of NDV in backyard chickens was also determined through a cross-sectional study conducted from June to August 2016. Based on ELISA results, the average seroprevalence of NDV at bird level was 33.8% (95%CI 31-36) and at flock level, 57.1% (95%CI 44-60%). However, there was no statistical difference in the NDV seroprevalence at flock and bird (P>0.05) levels among regions of Oman. The study findings indicate that ND is endemic in Oman. A questionnaire-based survey was used to investigate the risk factors for ND in the various poultry management systems in Oman. A response rate of 58% (n=857) was obtained. Thirty-eight percent of the respondents practiced the backyard system, whereas 54% and 28% of them were using open and close systems, respectively. The proportions of respondents with or without recorded ND outbreaks in their farms were 40% and 27%, respectively. However, 32% had no such information at their disposal. The backyard system had a significant association (OR=1.81, 95%CI 1.1-4.35) with the farms reporting ND compared to the close system. Farms lacking the service of a veterinarian (OR=5, 95%CI 1.98-14.5); the usage of dead vaccine (OR=2.3, 95%CI 1.2-4.2); farms not restricting visitors’ entry (OR=6.4, 95%CI 2.0-20.3) and usage of temporary staff (OR=3.9, 95%CI 1.5-10.6) were significantly associated with ND outbreaks reporting. Only 16% of the farmers reported ND outbreaks in their farms to the appropriate authority. A higher proportion (57%) of the farmers stop the sales of chickens while only 27.8% and 13.9% restrict production or submit samples to veterinary clinics during outbreak. There was a significant positive weak correlation between farms with recorded ND outbreaks and those that stop sales of chicken products (r=0.12, P=0.03) and restricting of production (r=0.17, P=0.002) during outbreaks. Newcastle disease virus isolated during this study characterized the NDV causing the outbreaks in Oman in 2017 which involved three poultry farms in Al-Dakhiliyah and Al-Batinah. Haemagglutination inhibition (HI) test and reverse transcription-polymerase chain reaction (RT-PCR) assay were used. The findings revealed that the Oman isolates showed high homology (98%) with other reported NDV isolates genotype VIIi which was previously isolated in Pakistan and considered to be highly pathogenic NDV. The results from the economic impact assessment study on the poultry industry in Oman due to ND outbreaks using three scenarios estimated the direct impact at about 2, 11 and 21 million Omani Rial, respectively, at mortality rate of 10% due to lentogenic, 50% mesogenic and 90% velogenic strains of NDV, respectively. In conclusion, ND and NDV are endemic in the poultry industry in the Sultanate of Oman. Backyard poultry is the most affected management system. Measures to reduce the occurrence of ND in backyard chickens could help prevent the spread to commercial flocks. Also, improving the management of chickens based on the factors associated with ND might contribute to effective preventive and control programme. More efforts by the authority in veterinary services are required to reduce the impact of the disease thus minimize the economic losses to the poultry industry of Oman.